Regional Mean Sea Level Changes in the German Bight - Albrecht, Frauke (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2013)
Regional mean sea level changes of the German Bight are analysed. The time span considered ranges from the mid of the 19th until the end of the 21st century. Tide gauge data from 15 locations are used to analyse past regional mean sea level changes. From these data, a time series representing the regional mean sea level of the German Bight is reconstructed following two different approaches. From both approaches comparable long-term trends are obtained from 1924 onwards. For the period 1924-2008 these trends are 1.64 mm/yr and 1.7 mm/yr, respectively. Also inter-annual and decadal variability from both approaches is comparable from 1924 onwards. Results before 1924 largely depend on data from a few stations only, in particular from Cuxhaven which is longest record available dating back until 1843. Thus, it is analysed to what degree the tide gauge of Cuxhaven is representative for the German Bight. The test was made for the period from 1924 onwards where data from most tide gauges were available. It was found that data from Cuxhaven do not reflect the common signal from all tide gauges and thus Cuxhaven does not provide a good proxy for sea level changes in the German Bight. It is assumed that this is mainly a result from different construction works. However, it can not been excluded that Cuxhaven has been representative before 1924. Decadal trends are analysed to detect a possible acceleration in the mean sea level time series. The result shows that decadal trends in the most recent periods were relatively high. However, when compared with earlier periods they are not extraordinary high. Subsequently, the impact of large-scale atmospheric pressure changes to the regional mean sea level is analysed. A statistical model between the regional mean sea level in the German Bight and the large-scale sea level pressure field over the North Atlantic is developed, using multiple linear regression. For the time period 1924-2001 it was found that the sea level pressure explains 58% of the inter-annual variability and 33% ...